2020
DOI: 10.32615/ps.2020.045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light intensity on the growth, photosynthetic characteristics, and secondary metabolites of Eleutherococcus senticosus Harms

Abstract: In this investigation, we used the growth, photosynthetic physiological parameters, and targeted metabolite analysis to evaluate the responses of Eleutherococcus senticosus in different shading treatments. The results showed that the moderate shading treatment (Z1) promoted the growth and inhibited photosynthesis of plants. The severe shading treatment (Z2) inhibited both the growth and photosynthesis of the plants. Besides, Z1 had no significant effect on the PSII, while Z2 inhibited the PSII. Most of the eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The accumulation and transportation of photosynthetic products in plants affect the formation of plant yield and quality (Dong et al 2019). By changing the canopy temperature, photosynthetic rate, heat dissipation, and pigment profile, the photosynthetic products of plants under shade treatment increased that affected the content and quality of polysaccharides as reported earlier (Xu et al 2020). The polysaccharide content of Codonopsis pilosula increased significantly under 44.8% illumination intensity (Wang et al 2017).…”
Section: Discussionsupporting
confidence: 54%
“…The accumulation and transportation of photosynthetic products in plants affect the formation of plant yield and quality (Dong et al 2019). By changing the canopy temperature, photosynthetic rate, heat dissipation, and pigment profile, the photosynthetic products of plants under shade treatment increased that affected the content and quality of polysaccharides as reported earlier (Xu et al 2020). The polysaccharide content of Codonopsis pilosula increased significantly under 44.8% illumination intensity (Wang et al 2017).…”
Section: Discussionsupporting
confidence: 54%
“…Light intensity also affects the chemical composition of medicinal plants. For instance, Xu et al (2020) fond that moderate shade (38.8% of the control) promoted the accumulation of C 6 C 1 -and C 6 C 3 -type phenolics, while severe shading (16.9% of the control) stimulated the accumulation of C 6 C 3 C 6 -type phenolics in Eleutherococcus senticosus. Santos Lazzarini et al ( 2018) treated Lippia gracilis with different light intensities and showed that the chemical composition of seedlings in the 26 μmol m −2 s −1 group was more complex, with more monoterpene hydrocarbons and less aromatic monoterpenes, than those in other treated groups.…”
Section: Light Intensitymentioning
confidence: 98%
“…However, plants under low (14.4%) irradiance showed significantly lower PN than plants under high and medium irradiance (Fig. 3), similar to A. roxburghii and Eleutherococcus senticosus (Shao et al 2014, Xu et al 2020. Under low irradiance conditions, insufficient ATP is produced for carbon fixation and carbohydrate biosynthesis, thus causing a decrease in PN.…”
Section: Morphological and Photosynthetic Responses To Different Ligh...mentioning
confidence: 75%